Input-output based analysis of intersectoral linkages for economic diversification in Oman - Hakro, Ahmed Nawaz; Farsi, Alya Al (Asian Development Policy Review, 2026)
The paper aims to quantify the intersectoral linkages that facilitate economic diversification in the Omani economy. The input-output analysis is used to assess the effects of inter-sectoral transactions for policy changes. The analysis is employed in development planning, impact assessment, and measuring external shocks. The short-run projected demand is forecasted through hypothetical positive and negative changes in final demand in each sector to predict changes in final demand. Income multipliers are derived by transposing the third-degree power series generation of the Leontief inverse matrix. The results suggest that the non-mining and quarrying sectors are strongly linked, with significant forward and backward linkages in determining value addition, output growth, and employment levels. The wholesale retail, fishing, public services, defense, health, and education sectors are creating employment opportunities. However, the employment and income multipliers indicate strong links with non-mining and services sectors. Policymakers should consider focusing on industries with strong connections. The robust linkages in the non-mining and quarrying sectors suggest that interventions in these sectors could help diversify the economy. The Omani economy requires an in-depth understanding of structural patterns, sectoral-level interventions, and consistency in policy measures.